Perkembangan Bahasa Anak Usia Dini dalam Extended Family - Afifah, Dhita; Mita, Angelina Risa Sonia; Sarmila, Sarmila; Juventy, Anastasya Ameliya; Pertiwi, Adharina Dian (Universitas Hamzanwadi, 2023)
Parents have a role in regulating the behavior and caring for their children as they grow to a certain age-appropriate development. Not sometimes, there are still many parents who educate their children according to their own idealistic point of view. This has quite an impact on children's language development, because the parents' demands on children are higher. So the more active the child's personality, the more parents hope they will. The impact of parenting patterns also has a significant effect if more than one type of family applies different parenting patterns. The aim is to determine the influence of the Extended Family on early childhood language development. Using a comparative methodology, Qualitative Research is research collected from observations in the field. The results are a comparison of the impact of early childhood language development and understanding in extended families. The researcher used three samples, where the first sample, initialed with A, had the influence of a democratic and permissive parenting style, the second child, initialed with B, had a democratic parenting style, and the third child, initialed with C, had a permissive parenting style. The results of the research are the Extended Family environment influences children’s language developement, through daily interactions and communication within their families.